Accelerated learning case study: Teaching introductory C and C++ - Pinpin, Lord Kenneth M. (Animo Repository, 2004)
The challenge in teaching a large class of sophomore students their first course in C and C++ are identified. Most of these problems stem from the way the course material is traditionally taught: giving two one-hour lecture sessions and one three-hour laboratory session per week to a class of 40 to 45 students. Motivated by the need to improve the amount of learning imparted, the authors implemented radical changes in the way the lecture and laboratory sessions were conducted. The techniques and innovations used are reported in this paper. The results are promising. Students reported better enthusiasm and confidence in programming, and the instructors reported the students had better programming skills, converted more material in less time, and were better able to manage the large class of students.